Mass Media and Public Policy : Global Evidence from Agricultural Policies - Olper, Alessandro; Swinnen, Johan (World Bank, Washington, DC, 2013)
Mass media play a crucial role in information distribution and in the political market and public policy making. Theory predicts that information provided by the mass media reflects the media's incentives to provide news to different groups in society and affects these groups' influence in policy making. The paper use data on agricultural policy from 69 countries spanning a wide range of development stages and media markets to test these predictions. The empirical results are consistent with theoretical hypotheses that public support for agriculture is affected by the mass media. In particular, an increase in media (television) diffusion is associated with policies that benefit the majority to a greater extent and is correlated with a reduction in agriculture taxation in poor countries and a reduction in the subsidization of agriculture in rich countries, ceteris paribus. The empirical results are consistent with the hypothesis that increased competition in commercial media reduces transfers to special interest groups and contributes to more efficient public policies.